Role Of High-Resolution Computed Tomography (Hrct) Temporal Bone In Different Pathologies (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: - High Resolution Computed Tomography (HRCT), a modification of routine CT, provides a direct  visual window in the temporal bone providing minute structural details [1]. Purpose of the  present study was to evaluate the normal variations, pathological processes (infections and  congenital anomalies) and their extent involving the temporal bone along with their  complications on HRCT and to correlate these imaging findings surgically. Aim of the Study: - To find out about the causes, different types of pathologies, male female ratio, and  management accordingly. Materials and Methods: - The prospective study included 100 patients who were presented to ENT department of AMC  MET MEDICAL COLLEGE with clinically suspected temporal bone or ear pathologies. After  detailed clinical examination, the patients were subjected to high resolution computed  tomography (HRCT) examination and most of them underwent surgery. The imaging findings  were correlated with the surgical findings. The surgical findings were considered as final. Observation and Results: - Of 100 cases examined, we had 93 cases of middle ear cleft pathology (chronic Otitis media,  cholesteatoma, soft tissue densities without cholesteatoma) out of which 25 cases were  cholesteatoma, 22 cases of soft tissue density in mastoid cavity and 46 cases had middle ear  opaque homogenous densities, 4 traumatic cases & 2 congenital pathology. Conclusion: - HRCT is a revolutionary imaging modality that helps in evaluating the distribution features,  localization and assessing the extent of various pathologies affecting the temporal bone. The  clinical and radiological findings showed a high level sensitivity with intraoperative findings as  regards to the presence of cholesteatoma, changes of the ossicular chain and erosion of the  lateral semicircular canal. Where criteria for cholesteatoma was soft tissue density in middle ear or mastoid with bony erosion, other cases in this study were 2 congenital cases in which the  findings of HRCT were in co-relationship with the intraoperative finding. One case of facial  nerve schwannoma was diagnosed on HRCT and confirmed intraoperatively. 4 cases of trauma  that stated fracture of longitudinal segment of temporal bone with facial palsy. One needed  surgical exploration for facial nerve decompression rest all improved by conservative management. Hence HRCT was very sensitive and specific with various pathologies confirmed  intraoperatively.
Keywords: Cholesteatoma; Chronic suppurative otitis media; high resolution computed tomographic scan; temporal bone pathology